Analisis Keterampilan Bermain Bola Basket pada Olimpiade Tokyo 2020 Melalui Aplikasi ESPN: Studi Kasus Men’s Gold Medal Game USA Vs FRANCE - Yuen Cheilo Prasetyo; Tokyo Olympics (Institut Nalanda, 2024)
According to Dean Oliver (2004), there are four important factors in determining a team's victory, namely: 1. Field goals (FGA which consists of 2 points and 3 points), 2. Free throw (FT), 3. Offensive rebound (OR) , 4. Turnover. These four factors are important things that coaches and athletes must know so that they can evaluate the previous match and improve it for the next match. Based on the problem formulation and problem boundaries that have been written, the researcher can write down the aim of this research, namely to find out how field goals (a combination of 2 points and 3 points), free throws, offensive rebounds and turnovers in the 2020 Tokyo Olympics match.This research is quantitative descriptive. The population in this study were USA and FRANCE basketball players. The samples in this study were USA players and FRANCE players who took part in the basketball match in Tokyo 2020. In this research the instrument used was match statistics at the Tokyo 2020 Olympics. This research used data collection techniques with documents, namely in the form of data from statistical results from matches between USA VS FRANCE at the 2020 Tokyo Olympics using the ESPN application.From the research data, it can be seen that the average 2points (2P) shot by one team in a match is 80%. The average 3points shot (3P) by one team in a match is 38%. One team's average free throw (FT) shot in a match is 60%. The average offensive rebound (OR) for a team in a match is 12 times. And the average turnover (TO) for a team in a match is 15 times. If converted to the percentage proposed by Dean Oliver, the 2points (2P) indicator has the largest percentage, namely 18.64%, followed by the 3points (3P) indicator, namely 11.18%, free throw (FT) 9.55% , offensive rebound (OR) 2 times, and turnover (TO) 4 times. This data can be used to determine the minimum number and percentage so that a team can win a basketball match at the 2020 Tokyo Olympics. When looking at the results of 12 matches, all winning teams have exceeded these percentages and amounts. The research conclusions are: 1. The average number of shots and the percentage of 2 points (2P) is 40 with a percentage of 80%. 2. The average number of shots and the percentage of 3 points (3P) is 19 with a percentage of 38%. 3. The average number of shots and free throw (FT) percentage is 30 with a percentage of 60%. 4. The number and average of offensive rebounds (OR) is 19 with an average of 12 offensive rebounds. 5. The number of numbers and average turnover (TO) is 21 with an average turnover of 15 times.